Renal cancer cells acquire immune surface protein through trogocytosis and horizontal gene transfer - Haley Q. Marcarian; Anutr Sivakoses; Anika M. Arias; Olivia C. Ihedioha; Benjamin R. Lee; Maria C. Bishop; Alfred L. M. Bothwell (PLoS ONE, 2025)
Trogocytosis is an underappreciated phenomenon that shapes the immune microenvironment surrounding many types of solid tumors. The consequences of membrane-bound proteins being deposited from a donor immune cell to a recipient cancer cell via trogocytosis are still unclear. Here, we report that human clear cell renal carcinoma tumors stably express the lymphoid markers CD45, CD56, CD14, and CD16. Flow cytometry performed on fresh kidney tumors revealed consistent CD45 expression on tumor cells, as well as varying levels of the other markers mentioned previously. These results were consistent with our immunofluorescent analysis, which also revealed colocalization of lymphoid markers with carbonic anhydrase 9, a standard kidney tumor marker. RNA analysis showed a significant upregulation of genes typically associated with immune cells by tumor cells. Finally, we show evidence of chromosomal DNA being transferred from immune cells to tumor cells through physical contact. This horizontal gene transfer has transcriptional consequences in the recipient tumor cell, resulting in a fusion phenotype that expresses both immune and cancer specific proteins. This work demonstrates a novel mechanism by which tumor cell protein expression is altered through the acquisition of surface membrane fragments and genomic DNA from infiltrating lymphocytes. These results alter the way in which we understand tumor-immune cell interactions and may reveal new insights into the mechanisms by which tumors develop. Additionally, further studies into trogocytosis and other mechanisms of contact-mediated cellular transfer will help push the field towards the next generation of immunotherapies and biomarkers for treating renal cell carcinoma and other cancers.